Effects of pressure and velocity on the interface friction behavior of diamond utilizing ReaxFF simulations. (1st February 2021) - Yuan, Song; Guo, Xiaoguang; Mao, Qian; Guo, Jiang; van Duin, Adri C.T.; Jin, Zhuji; Kang, Renke; Guo, Dongming
Highlights: Friction force depends on the number of interfacial C-C and C-O-C bonds initially. Friction force relies on the number of amorphous carbon atoms later. C atoms are mainly removed in the form of C-C single bonds at low pressure. C atoms are removed in the form of C-C single and multiple bonds at high pressure. C-C bonds cause extensive atom removal, more severe wear and subsurface damage. Abstract: The effects of pressure and sliding velocity on the interface friction behavior during the chemical mechanical polishing process of diamond were investigated utilizing ReaxFF molecular dynamics, with a focus on the subsurface damage, friction force, and atom removal. Simulation results indicate that in the initial stage, the friction force depends on the number of interfacial C-C bonds and C-O-C bonds and shows a positive correlation with the pressure and sliding velocity. Later on, the friction force relies on the number of amorphous carbon atoms, and exhibits a negative correlation with the pressure and sliding velocity. Under low pressure, the carbon atoms are mainly removed along with the formation of C-C single bonds. In contrast, with increasing pressure, the carbon atoms are removed together with the formation of more C-C single and multiple bonds. This accounts for more extensive atom removal, followed by the more severe wear, as well as deeper subsurface damage. This study systematically evaluates the underlying influence mechanism of pressure and sliding velocity on the interface friction behavior from atomistic scale, thus elucidating technological parameters for ultra-precision and low-damage machining of diamond. Graphcial abstract: Image, graphical abstract